BAIK DAN BURUK SERTA POKOK-POKOK KEUTAMAAN AKHLAK - Harahap, Hendra Asri; Habibah, Elia Nur; Wulandari, Elisa; Abidin, Jaenal; Saefina, Khaila Najwa; Sitika, Achmad Junaedi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2023)
Good and bad are simple because they have meanings that indicate a situation. The meaning of good and bad can also be understood generally and naturally so that it is considered a normal thing, but behind that the words good and bad have a very broad meaning. In Arabic, good is khair. Good can also be said to be something that has reached perfection and can also be said to be something that gives rise to feelings of joy, satisfaction, harmony and so on. On the other hand, bad actions are the opposite of good things, humans can be said to be good when they do not do bad things. Good and bad have a measure to be able to judge human actions. And there are also schools of thought about good and bad such as hedonism, naturalism, vitalism, eudemonism, utilitarianism and deontology. This is the basis for humans to always do good and avoid evil in everyday lifeKeyword : Good and bad, size, flow of thought